1992
DOI: 10.1007/bf00877245
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical trial and pharmacokinetic evaluation of doxorubicin carried by polyisohexylcyanoacrylate nanoparticles

Abstract: Doxorubicin (DXR) incorporated into biodegradable acrylate nanoparticles such as polyisohexylcyanoacrylate (PIHCA) has been shown to increase DXR cytotoxicity and reduce cardiotoxicity by modifying tissue distribution in preclinical studies. We have conducted a phase I clinical trial of DXR-PIHCA in 21 patients with refractory solid tumors (10 male, 11 female, median age: 53 years, median PS: 1, prior free-DXR therapy: 7 patients). A total of 32 courses at 28 day intervals were administered at 6 dose levels (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(58 citation statements)
references
References 14 publications
2
55
0
1
Order By: Relevance
“…17 Lacking stealth properties, poly(alkylcyanoacrylate) nanoparticles administered intravenously are rapidly cleared from the blood stream by the monuclear phagocyte system (MPS) and mainly accumulate in liver and spleen, 18 -20 together with the entrapped compounds. [21][22][23] Only pegylated polyalkylcyanoacrylate nanoparticles have lower MPS uptake and prolonged blood circulation in vivo.…”
Section: General Considerationsmentioning
confidence: 99%
“…17 Lacking stealth properties, poly(alkylcyanoacrylate) nanoparticles administered intravenously are rapidly cleared from the blood stream by the monuclear phagocyte system (MPS) and mainly accumulate in liver and spleen, 18 -20 together with the entrapped compounds. [21][22][23] Only pegylated polyalkylcyanoacrylate nanoparticles have lower MPS uptake and prolonged blood circulation in vivo.…”
Section: General Considerationsmentioning
confidence: 99%
“…Cancer therapy for instance is severely limited by the toxicity caused by the antitumor agents on normal cells. Doxorubicin treatment is associated with severe cardiotoxicity and hepatotoxicity, but when it was administered using nanoparticles, neither of theses side effects were observed due to the localization of the nanoparticle formulation to the tumor (Kattan et al, 1992). It is critical that the drug delivery vehicle does not upset the normal physiology of the biological system, while exploiting the unique pathophysiological characteristics of diseased tissue or cell.…”
Section: Clinical Aspects and Future Perspectivesmentioning
confidence: 95%
“…[148,149] Clinical trials have even shown that these nanodevices are safe and biocompatible when loaded with the anticancer drug doxorubicin. [150] Nicolas et al [151] proposed a general methodology to prepare highly functionalized PACA nanoparticles by means of Huisgen 1,3-dipolar cycloaddition. To achieve this goal, different protocols were investigated to obtain azido PEG cyanoacrylate of variable molar mass, followed by a Knoevenagel condensation-Michael addition reaction with hexadecyl cyanoacrylate to produce a poly[(hexadecyl cyanoacrylate)-co-azido poly(ethylene glycol) cyanoacrylate] [P(HDCA-co-N 3 PEGCA)] copolymer, displaying azide functionalities at the extremity of the PEG chains.…”
Section: Polymeric Surfacesmentioning
confidence: 99%